Graded early warning for crude oil tanks based on TOPSIS - Gang WU; Shuxin ZHANG; Jinheng LUO; Lifeng LI; Ri XU; Qingquan DUAN; Yifan WANG (You-qi chuyun)
Objective Given the rise in large-scale and centralized crude oil tanks, along with the physical and chemical properties of crude oil and the intricate nature of tank materials and components, these tanks present substantial risks. Consequently, enhancing the risk management capabilities of tank farms becomes imperative to enable enterprises overseeing routine tank management to acquire a comprehensive grasp of tank conditions. However, the prevailing risk-based inspection technology, mandated by current foreign standards, poses challenges in practical execution, primarily due to the extensive field data requirements. Moreover, there is a lack of impact analysis focusing on tank accessories in the assessment of equipment factors. Methods This paper presents a graded early warning system for crude oil tanks, incorporating a model based on the Technique for Order Preference by Similarity to an Ideal Solution(TOPSIS) to facilitate a comprehensive assessment and graded early warning of tank risks.(1) The established system of tank risk assessment indicators includes 4 primary indicators of human, equipment, environment, and management factors and several secondary and tertiary indicators.(2) The Analytic Hierarchy Process is integrated to assign weights to indicators at different levels, and the TOPSIS method is utilized to calculate the relative proximity of tanks.(3) Risks are ranked to enable graded early warning for tanks according to the results of relative proximity. Results The graded early warning of risks was carried out for 4 crude oil tanks located at a crude oil depot in western China. The assessment results closely aligned with those derived from API 581-2016 Risk-based Inspection Methodology and EEMUA 159-2017 Above Ground Flat Bottomed Storage Tanks: A Guide to Inspection, Maintenance and Repair.This alignment proved the efficacy of the proposed system in early warning, highlighting its convenience in execution and its coverage of more assessment indicators. Conclusion The study results serve as rational references for tank farm patrol inspections and tank overhaul scheduling.